(untitled) (Al-Academy, 2023)
When a person found himself in a life he did not understand، he tried to create in his imagination powers and gods that tried to protect him from his ignorance of that world، and when he was reassured internally through those fantasy creatures when he made them the greatest protector and the source of his existence and his being، he began to weave myths and myths until he created his reality that he did not have. Any hint، and when we go back to the mechanism of embodying those myths، myths and fantasias in which he lived، we will find that the first building blocks were written on the walls of the caves in which he lived during that period. And when his thought developed and thus his expressive means developed، he began to embody this undisciplined fantasy through means that fit his era and his thought، which he tried to make it more in contact with the reality he lives in so that it is thus an analogy between that fantasy and the realism he lives in، and for this you see him continuing to develop his productions and weave them in a way The realistic and the fantasy blend in a form component that is in line with the recipient’s awareness and horizon of expectation regarding the narrated material. Accordingly، the subject of the aesthetic employment of alliteration formed a central position in animated films، due to the fact that this type of films possesses undisciplined material in terms of the fantasy that it deals with realistically. Hence the research problem came as follows: (What is the aesthetic employment of realistic and fantasy anagrams in animated films?)